A179 EXPLORING RELATIONSHIPS BETWEEN HANDGRIP STRENGTH, MID-UPPER ARM CIRCUMFERENCE, SUBJECTIVE GLOBAL ASSESSMENT AND ADVERSE CLINICAL OUTCOMES IN CIRRHOSIS: A PROSPECTIVE COHORT STUDY. (15th March 2019) - Wishart, E; Taylor, L; Lam, L; Marr, K J; Stapleton, M; Fitzgerald, Q; Chiu, E; Tandon, P; Raman, M
Abstract: Background: Malnutrition is highly prevalent in cirrhosis and is an independent predictor of negative clinical outcomes. Nutrition assessment (NA) is often not performed in patients with cirrhosis and this may result from a lack of clarity surrounding valid bedside tools. Aims: The study aimed to identify relationships between baseline NA measurements and adverse clinical outcomes in patients with cirrhosis. Methods: A prospective cohort study was conducted between 2014–2018 at the University of Calgary. Ambulatory pre-liver transplant patients with cirrhosis were co-assessed by a registered dietitian and a physician nutrition specialist in a specialized malnutrition clinic, and completed measurements of subjective global assessment (SGA), handgrip strength (HGS) and mid upper arm circumference (MUAC). Clinical outcomes including frequency of hospitalizations, length of stay, infections, and hepatic encephalopathy were collected in the 6–12 months following nutrition assessment. Mortality was examined from baseline to 3 years. T-tests and chi-squared analyses were used to examine relationships between NA tools and clinical outcomes. Results: This study included 66 patients, mean age 54 (±10.1) years, and 56% (n=37) male. Baseline demographic characteristics are summarized in Table 1. Malnourished SGA status (9.5% (n=2) SGA A vs. 90.5% (n=19) who were SGA B and C) and lower HGS category (23.8% (n=5) who had a higher HGS vs. 76.2% (n=16) with a lower HGS) both had significantly higher proportions of mortality (SGA: (χ 2 (2)=6.6, p<0.05); HGS: (χ 2 (1)= 15.9, p<0.001), while MUAC was not significantly related to mortality (χ 2 (1) =1.9, p =0.17). The probability of a mortality event was 3.2 times more likely when they were in a lower HGS category. Higher MELD category was also associated with increased mortality (χ 2 (1) =4.1, p =0.04). SGA, HGS and MUAC were not significantly related to the other clinical outcomes. Conclusions: In our study, malnutrition diagnosed by both SGA and HGS is predictive of mortality in cirrhosis. Incorporating SGA and HGS into routine clinical practice for pre-liver transplant patients with cirrhosis to identify patients who may benefit form nutrition therapy should be considered. Funding Agencies: Baxter Canada